The Impact of Brand Awareness, Brand Loyalty, and Brand Association on Consumer Decision Making in Palestine Olive Oil Industry - Suhail A M, Almaqousi; Siti Aida, Samikon; Luigi Pio Leonardo, Cavaliere; Nordiana, Ahmad Nordin (Macrothink Institute, 2021)
Brands come to play an essential role to motivate and stimulate the consumer to take actions that satisfy their needs and desires with obtaining the brand that according to their perception meets the requirements and possibilities. In par with the same, researchers have focused on studying the impact of brand awareness, brand loyalty, brand association and consumer decision making on Palestine olive oil industry. The research approach of the study is deductive discipline and primary data were gathered followed by a structured questionnaire. The relationships between each selected variables and consumer decision making were examined along with hypotheses developed. For that, empirical data is collected from the olive oil stakeholders from Palestine. The results show that there is a significant statistical relationship between these variables. Moreover, the brand awareness, brand loyalty and brand association significantly have the positive effects on the consumer decision making. The managerial implications have been discussed specially referring to the contexts brand awareness and loyalty as to make decision through this study